Synthesis of Carboxymethyl Cellulose (CMC) from Banana Tree Stem: Influence of Ratio of Cellulose with Sodium Chloroacetate To Properties of Carboxymethyl Cellulose - Hendrik Aditya Mulyatno; Odisaputra Ihsan Pratama; Inayati Inayati (Equilibrium Journal of Chemical Engineering, 2017)
Banana tree stem contain of 63-64% cellulose that can be processed into more valuable product. In this research, carboxymethylcellulose (CMC) from banana tree stem was  prepared  through  alkalization  and  carboxymethylation process.  The  aim  of  this research was to investigate the effect of cellulose to sodium chloroacetate 1:1 and 1:2 to the properties of CMC. Samples were analyzed their NaCl content, purity of CMC, and degree of substitution. The result showed that sample with ratio 1: 2 between cellulose with sodium chloroacetate resulted greater NaCl content, lower purity of CMC, and greater degree of substitution.